Effect of RRA heat treatment on corrosion and mechanical properties of AA7075 - Ozer, Gokhan; Karaaslan, Ahmet (WILEY-V C H VERLAG GMBH, 2019)
In this study, a retrogression process (R) has been applied to AA7075 at 180, 240, and 370 degrees C for 15, 30, 90, and 120 min. After the retrogression, reaging treatment (RA) was reapplied with T6 conditions (120 degrees C for 24 hr). The effect of different temperatures and time periods of retrogression and reaging temper on exfoliation corrosion (EXCO) of the AA7075 is examined. The EXCO solution was prepared in accordance with the ASTM G34-01 standard and the samples were kept in the solution for 48 hr. Susceptibility of the alloy to EXCO was determined by weight loss detection, macro and microstructure studies, scanning electron microscope, transmission electron microscope, and energy dispersive X-ray analyses. The mechanical properties of aged samples were determined by hardness, tensile tests, and fractography.
Keywords: AA7075; exfoliation corrosion; mechanical properties; RRA; ALLOY; STRENGTH; Materials Science; Metallurgy & Metallurgical Engineering